Wearing the Cloth of Kain Tenun Tais: a Gender Differentiation and Status Symbol of the Bunaq Ethnic Group in West Timor-Indonesia - Lusius Tae Mau (Journal of Social Research, 2025)
This study examines the socio-cultural significance of Kain Tenun Tais within the Bunaq ethnic group of West Timor, Indonesia. Using a qualitative approach supported by descriptive statistics from a survey of 40 randomly selected respondents knowledgeable about the weaving tradition, the research explores the historical and contemporary roles of Kain Tenun Tais in Bunaq society. Findings reveal that the woven cloth serves as both a symbol of ethnic identity and a medium for preserving traditional knowledge, particularly through the oral narratives known as Tei Gugul Hiliq, which guide the creation of motifs and patterns. The designs, colors, and thread arrangements function as markers of social status, lineage, and gender, with certain motifs reserved for individuals of noble descent or specific ceremonial roles. The weaving process reflects a balanced gender partnership, where women are responsible for weaving while men contribute by preparing threads, constructing looms, and participating in ceremonies. Overall, Kain Tenun Tais functions as a living cultural artifact that embodies historical continuity, spiritual beliefs, and the social structure of the Bunaq community, ensuring the intergenerational transmission of identity and values.